The Role of Librarian Interpersonal Communication in Supporting Library Users' Information Literacy: A Systematic Literature Study - Dwi Rahmawati; Moh. Safii (Universitas Sebelas Maret Library, 2025)
Information literacy is a crucial key competency for library users in this era of abundant information, and its success is greatly influenced by the role of librarian communication. This study aims to analyze the transformative role of librarians' interpersonal communication in supporting users' information literacy thru a systematic literature review approach of ten articles published between 2015 and 2025. The research findings indicate that interpersonal communication plays a central role, reflected thru direct verbal interaction, nonverbal communication, digital media, an empathetic approach, and educational communication. Effective communication encourages users to access, evaluate, and utilize information independently and ethically. The effectiveness of this communication is supported by positive attitudes, empathy, the librarian's relational skills, as well as the use of technology and professional training. On the other hand, the challenges faced include limitations in basic skills, limitations in facilities such as cramped spaces and slow internet connections, and a lack of understanding of users' information needs. In conclusion, strengthening librarians' relational skills needs to be a priority for libraries to function optimally as information empowerment-oriented learning spaces.